2023
DOI: 10.3390/su15021371
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Modeling and Heritage: A Design Process Sustainable for Restoration

Abstract: Parametric design, algorithmic modeling, generative design, and associative design are only some of the keywords of a work paradigm that is becoming more and more popular, designed to respond to the complexities of contemporary architecture. Most commonly, such an approach is used for new buildings, but when algorithmic design meets heritage building information modeling (HBIM), the process can take on an even greater centrality—flexibility and control go hand-in-hand, ensuring precious tools for the planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The proposed new Master programme is expected to provide an significant impact within 3 levels: at system level, at institutional level, at individual level. (Liberotti and Gusella, 2023;Urbanowicz and Nyka, 2012). Numerous studies on Digital Databases and Information Systems have shown how digital practice can offer a common platform to integrate this different sectoral knowledge and to set a common basis of technical language and integrated 2D/3D products (Doria et al, 2022;Galasso et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed new Master programme is expected to provide an significant impact within 3 levels: at system level, at institutional level, at individual level. (Liberotti and Gusella, 2023;Urbanowicz and Nyka, 2012). Numerous studies on Digital Databases and Information Systems have shown how digital practice can offer a common platform to integrate this different sectoral knowledge and to set a common basis of technical language and integrated 2D/3D products (Doria et al, 2022;Galasso et al,2021).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, information management's topic within HBIM has been extensively addressed concerning data management to facilitate decision-making in preventive and planned conservation. If parametric modelling is combined with algorithmic modelling, it is possible to increase the levels of detail and reliability even to the knowledge of the historic built environment and thus to the design of restoration and asset management interventions [5]. Some more recent experiences have gone as far as translating qualitative data into numerical values to define a priority index for interventions [6] or deploying visual programming (VPL) as a tool to support the HBIM methodology, for example, for calculating the Masonry Quality Index, a parameter used for the seismic analysis of masonry [7].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, information management's topic within HBIM has been extensively addressed concerning data management to facilitate decision-making in preventive and planned conservation. If parametric modelling is combined with algorithmic modelling, it is possible to increase the levels of detail and reliability even to the knowledge of the historic built environment and thus to the design of restoration and asset management interventions [5]. Some more recent experiences have gone as far as translating qualitative data into numerical values to define a priority index for interventions [6] or deploying visual programming (VPL) as a tool to support the HBIM methodology, for example, for calculating the Masonry Quality Index, a parameter used for the seismic analysis of masonry [7].…”
Section: Introductionmentioning
confidence: 99%